2017
DOI: 10.1038/s41598-017-15402-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy on bone turn-over markers in men with type 2 diabetes and hypogonadism – a randomised controlled study

Abstract: Type 2 diabetes (T2DM) is associated with increased risk of fractures. Soy supplementation has been shown to have a beneficial effect on bone turnover markers (BTM) in postmenopausal women. However, the effect of soy supplementation on BTM in T2DM and particularly in men is unclear. We performed an analysis of a randomized double blind parallel study of 200 men with T2DM treated with soy, either with or without isoflavones. Outcome measures were type I collagen crosslinked beta C-telopeptide (βCTX), and type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…A significant linear correlation was also shown between βCTX reduction and glycated hemoglobin (HbA1) reduction. These results showed that the intake of soybean proteins containing isoflavones uses a mechanism to reduce βCTX related to blood glucose control and insulin tolerance enhancement by altering insulin resistance [225,226]. This confirmed that by altering insulin resistance in males with type 2 diabetes, the consumption of soy protein containing isoflavones for 3 months reduced βCTX, which is associated with the improvement of blood sugar control and insulin resistance [225].…”
Section: Improvement Of Blood Glucose Homeostasissupporting
confidence: 63%
See 1 more Smart Citation
“…A significant linear correlation was also shown between βCTX reduction and glycated hemoglobin (HbA1) reduction. These results showed that the intake of soybean proteins containing isoflavones uses a mechanism to reduce βCTX related to blood glucose control and insulin tolerance enhancement by altering insulin resistance [225,226]. This confirmed that by altering insulin resistance in males with type 2 diabetes, the consumption of soy protein containing isoflavones for 3 months reduced βCTX, which is associated with the improvement of blood sugar control and insulin resistance [225].…”
Section: Improvement Of Blood Glucose Homeostasissupporting
confidence: 63%
“…These results showed that the intake of soybean proteins containing isoflavones uses a mechanism to reduce βCTX related to blood glucose control and insulin tolerance enhancement by altering insulin resistance [225,226]. This confirmed that by altering insulin resistance in males with type 2 diabetes, the consumption of soy protein containing isoflavones for 3 months reduced βCTX, which is associated with the improvement of blood sugar control and insulin resistance [225]. The intake of soy isoflavones, furthermore, improves the blood glucose level and lowers the risk factors in type 2 diabetes patients.…”
Section: Improvement Of Blood Glucose Homeostasismentioning
confidence: 90%
“…37 Although several long-term RCTs (>6 months) indicated the remarkable effect of soy on BTMs, 41,42 clinical trials with shorter duration (50 days to 6 months) than our study also reported a significant effect on bone remodeling markers. 43,44 Soy isoflavones show weak estrogenic activity with an effectiveness that is incomparable with that of medications for osteoporosis. Thus, long duration is required to acquire favorable effect on the bone remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…As a phytoestrogen, numerous studies have focused on that genistein prevents bone loss and improve bone health through estrogen receptor pathway in both postmenopausal women and ovariectomized animals ( 18 ). Recently, an epidemiological study suggested that soy-containing isoflavones could reduce bone resorption significantly in men with T2DM, which correlated with an improvement of glycemic control ( 19 ). A small number of animal studies reported that genistein could enhance bone health of animals with T2DM and increase the bone strength ( 20 , 21 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%